Sustainable solid waste utilisation options for the historical city of istanbul - (:unkn) unknown (My University, 2006)
Sustainable disposal and utilization of solid waste is of utmost importance for Istanbul, the historically and geographically magnificent city of Turkey with its over 10 million inhabitants. The article shortly introduces the reader to the history and geography of Istanbul and underlines some important figures. The current efforts and projects undertaken by both the municipalities and private companies in order to utilize solid waste in a sustained way are described.